Examining marine pollution governance from the perspective of international investment law: theoretical connection, development trends, and China’s experience - Liu, Xue; Yu, Zhanyang (Frontiers in Marine Science, 2025)
Global marine pollution demands effective governance measures, with international investment law playing a crucial role. This study explores ocean pollution governance through international investment law, focusing on two aspects. First, it examines environmental clauses in investment agreements and their influence on host countries’ environmental regulatory space. Second, it assesses China’s current marine environmental laws and governance practices, highlighting challenges like insufficient legal integration and unclear liability definitions. Findings indicate a shift towards “greening” international investment rules, emphasizing the importance of environmental provisions in managing marine pollution. However, earlier treaties often lacked comprehensive environmental clauses, restricting host nations’ regulatory capacities. Accordingly, it is necessary to strengthen multilateral cooperation and refine specific rule innovations. By leveraging investment-rule reform platforms to promote the implementation of marine environmental regulations, the negative impacts of ISDS can be mitigated, ultimately achieving a win-win between investment protection and marine environmental conservation.